Optimization of Subcritical Water Hydrolysis of Corncob for Reducing Sugar Production as Bioethanol Feedstock - ตุนชัยภูมิ, สุรวิทย์ (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2018)
Corncob is one of the Thai agricultural residues which are classified as lignocellulosic material, it can be converted to reducing sugar as bioethanol feedstock. The purpose of this research was the optimization of reducing sugar production form corncob using subcritical water (SCW) hydrolysis. Response surface methodology (RSM) with box-behnken design was employed to optimize hydrolysis conditions: temperature (170-210 oC), time (30-90 min) and raw material to water ratio (R/W ratio)(1:10-1:30). The RSM results indicated that SCW hydrolysis conditions (temperature, time and R/W ratio) could significantly affect reducing sugar yield (P<0.05), the optimization of SCW hydrolysis conditions were as follows: 193 oC, 44 minutes and R/W ratio as 1:30, which gave the highest reducing sugar yield of 32.54% g/g dried raw material. Moreover, the SCW hydrolysis gave amount of reducing sugar which was higher than using acid hydrolysis at time of 60 min as 1.4 times.